Konsep Perancangan dan Penyusunan Proposal Penelitian - Dinil Abrar Sulthani (Jurnal Ilmiah Dikdaya, 2023)
This paper describes the concept of design and preparation of research proposals. This topic was chosen as an alternative solution to overcome common problems that are often encountered by researchers in writing research proposals. This paper helps researchers and readers to prepare research proposals properly and correctly. This paper is discussed using a type of qualitative research method with a library research approach. This literature paper was written with data sources from reading books, relevant journals, and input comments from research class seminars and the author's experience during research. The results of this paper indicate that in the design and preparation of research proposals, it is necessary to pay attention to the important elements in the proposal. Important elements include the accuracy of determining the topic or research theme, writing a clear background of the problem, identifying the problem, formulating research with problem questions and then limiting the problem so that it is more focused and concerned in the research, as well as writing research objectives that are correlated with the formulation of the problem. The conclusion of this paper is that a good research proposal is prepared based on preparation and a good understanding of the elements of the research.